Does foreign aid really raise per capita income?: a time series perspective - Nowak-Lehmann D., Felicitas; Dreher, Axel (The Canadian journal of economics, 2012)
We analyze the relationship between per capita income and foreign aid. We employ annual data and five-year averages and carefully examine the time-series properties of the data. Panel estimations with dynamic feasible generalized least-squares (DFGLS) show that aid generally has an insignificant or minute negative significant impact on per capita income (particularly in highly aid-dependent countries). This holds true for countries with different levels of human development and income, as well as for different regions. We also find that aid has a small positive impact on investment, but a significant negative impact on domestic savings (crowding out) and the real exchange rate (appreciation).